Inclusive history education - Busch, Sebastian (Kleine Reihe - Geschichte, 2025)
Inclusion brings with it new challenges for the planning of history lessons. The increasing heterogeneity of the student body also demands new ways of differentiation and subject orientation from history teachers. This volume brings together ideas and practical examples to meet these challenges and provide teachers with guidance when designing history lessons in inclusive classes. The focus is on diagnostics and individual support planning. In addition, general principles of inclusive teaching such as the Universal Design of Learning, language sensitivity and aesthetic approaches to historical learning are presented. The volume is not solely focused on inclusive teaching for children and young people with special educational needs. Rather, it is based on a broad understanding of inclusion that takes school diversity as a whole into account.